Effects Of Leadership Styles And Interactional Justice On The Use Of Upward Influence Tactics: An Experimental Study - Mohamed Zainal, Siti Rohaida (2002)
The purpose of this study is to examine the effects of the interaction between leadership styles and interactional toward upward influence tactics. This study use 2 (leadership styles: participative/autocratic) X 2 (interactional justice: fair/unfair) X 2 (gender of the supervisor: male/ female) between-subjects factorial design. Since this is an experimental study, promotion is being used as career objective of the employees. In total, there are eight different scenarios involve in this study.